2020
DOI: 10.3390/ijerph17041250
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Canadian Packaged Food Supply Using Health Canada’s Proposed Nutrient Criteria for Restricting Food and Beverage Marketing to Children

Abstract: Federally mandated restrictions on food and beverage marketing to kids (M2K) have been re-introduced as a national public health priority in Canada by the newly elected government, following the failure to implement a similar policy first proposed in 2016. This study examined the extent to which Canadian packaged foods, including products already displaying M2K on the packaging, would be permitted to be marketed, based on the nutrient criteria for marketing restrictions defined by Health Canada (in December 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 16 publications
2
13
0
Order By: Relevance
“…Although the generic food composition database (i.e., CNF 2015) showed a lower prevalence of a FOP symbol among foods commonly consumed by Canadians, the branded database (i.e., FLIP 2017), showed that over 60% of packaged products would be deemed “less healthy” according to the proposed FOP labelling regulations (i.e., ‘high in’ one or more nutrients-of-concern). Consistent with our findings, much evidence has shown that the Canadian packaged food supply is dominated by energy-dense and nutrient-poor food and beverage products that are often highly processed [ 25 28 ]. Increased consumption of highly processed foods may be linked to poor diet quality and adverse health outcomes [ 30 , 31 ], in part, related to the elevated amounts of nutrients-of-concern.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although the generic food composition database (i.e., CNF 2015) showed a lower prevalence of a FOP symbol among foods commonly consumed by Canadians, the branded database (i.e., FLIP 2017), showed that over 60% of packaged products would be deemed “less healthy” according to the proposed FOP labelling regulations (i.e., ‘high in’ one or more nutrients-of-concern). Consistent with our findings, much evidence has shown that the Canadian packaged food supply is dominated by energy-dense and nutrient-poor food and beverage products that are often highly processed [ 25 28 ]. Increased consumption of highly processed foods may be linked to poor diet quality and adverse health outcomes [ 30 , 31 ], in part, related to the elevated amounts of nutrients-of-concern.…”
Section: Discussionsupporting
confidence: 91%
“…The Food Label Information Program (FLIP) is a branded food database developed and maintained by the University of Toronto, details for which have been published elsewhere [18,[23][24][25][26][27][28]. Briefly, FLIP 2017 data was collected between May and September 2017 and contains nutritional information for 17,671 unique packaged food and beverage products from top Canadian food retailers (Loblaws, Sobeys and Metro), representing approximately 64% of the retail market share at the time of collection.…”
Section: Food Label Information Program (Flip) 2017mentioning
confidence: 99%
“…For example, when the exact same sample of 374 child-directed supermarket products was analysed using three different nutrient profiling models, the percentage of products permitted to be marketed to children varied dramatically, from 3% of products permitted to 29% [68]. A subsequent study, applying five different nutrient criteria to the same child-directed products, reported similar results [69]. Studies such as these underscore the critical nature of the nutrient criteria used, given the remarkable span between the number of products permitted to be marketed to children depending on the nutrient profiling model-from one in 50 products permitted to one in four.…”
Section: Considering Nutritional Quality and Nutrient Profiling Criteriamentioning
confidence: 88%
“…The determination of M2K on the labeling was conducted by observing the FoP of each product, and the presence of the following techniques was sought; use of characters, drawings, celebrities, athletes, children images, gifts, collectible packaging, playful packaging, contests, animated letters, or special colors and flavors [17,19]. If the same type of technique was repeated two or more times in the same product, it was considered as one.…”
Section: Methodsmentioning
confidence: 99%